STUDENTS’ ATTITUDE TOWARDS ONLINE SHOPPING & THE POSSIBILITY TO FACILITATE ITS GROWTH: A STUDY IN RAJSHAHI CITY, BANGLADESH - Hossain, S.M. Ashraf; Alam, Md. Shamsul (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
Many studies have been conducted on Bangladeshis' online shopping habits, but only some on students' attitudes. With the recent growth of online shopping worldwide and the unexplored potentiality in the country's northern region, this topic is worthy of deeper understanding. The main objective of this study is to have an in-depth knowledge of students' attitudes toward online shopping in Rajshahi city, Bangladesh. This study collected data from 87 randomly selected students from March 2022 to May 2022 from different educational institutions in the city. Various statistical tools, including mean, standard deviation, pie charts, column charts and Likert Scale, have been employed to examine the students' attitudes. The results of this study show that most students are proficient internet users, although they mostly use it for recreational purposes. However, 92% of them have shopped online at least once. Moreover, this study also revealed that the most frequently purchased products by the students are clothing (35%), books (30%) and electronic products (22%). The results from the Likert Scale analysis found that 36 students agree and 24 strongly agree that they are overall satisfied with their online shopping experience despite facing problems like late delivery and receiving damaged products. Therefore, the study's findings suggest that online retailers must focus on improving the marketing aspect of their business, ensuring the quality of their products and maintaining time flexibility throughout the delivery period.JEL Classification Codes: M20, M31, M37, M50.